Mapping Knowledge Structure and Research Frontiers of Ultrasound-Induced Blood-Brain Barrier Opening: A Scientometric Study - Wu, Haiyang; Zhou, Yan; Xu, Lixia; Tong, Linjian; Wang, Yulin; Liu, Baolong; Yan, Hua; Sun, Zhiming (Frontiers in Neuroscience, 2021)
Background: Among the effective approaches developed for blood-brain barrier (BBB) opening, ultrasound is recognized as a non-invasive technique that can induce localized BBB opening transiently and repeatedly. This technique has aroused broad attention from researchers worldwide, and numerous articles have been published recently. However, no existing study has systematically examined this field from a scientometric perspective. The aim of this study was to summarize the knowledge structure and identify emerging trends and potential hotspots in this field. Methods: Publications related to ultrasound-induced BBB opening published from 1998 to 2020 were retrieved from Web of Science Core Collection. The search strategies were as follows: topic: (“blood brain barrier” OR “BBB”) AND topic: (ultrasound OR ultrason* OR acoustic* OR sonopora*). The document type was set to articles or reviews with language restriction to English. Three different analysis tools including one online platform, VOS viewer1.6.16, and CiteSpace V5.7.R2 software were used to conduct this scientometric study. Results: A total of 1,201 valid records were included in the final analysis. The majority of scientific publication was produced by authors from North America, Eastern Asia, and Western Europe. Ultrasound in Medicine and Biology was the most prominent journal. The USA, China, and Canada were the most productive countries. Hynynen K, and Mcdannold N were key researchers with considerable academic influence. According to analysis of keywords, four main research directions were identified: cluster 1 (microbubbles study), cluster 2 (management of intracranial tumors), cluster 3 (ultrasound parameters and mechanisms study), and cluster 4 (treatment of neurodegenerative diseases). The current research hotspot has shifted from the basic research of ultrasound and microbubbles to management of intracranial tumors and neurodegenerative diseases. Burst detection analysis showed that Parkinson's disease, doxorubicin, gold nanoparticle, glioblastoma, gene therapy, and Alzheimer's disease may continue to be the research frontiers. Conclusion: Ultrasound-induced BBB opening research is in a period of robust development. This study is a starting point, providing a comprehensive overview, development landscape, and future opportunities of this technology, which standout as a useful reference for researchers and decision makers interested in this area.